The Effect of H-Hope Plus Kinesthetic with Acupressure ST 36 and SP 6 on Weight Gain among Infants with Low Birth Weight - Rizqitha Rizqitha; Mardiyono Mardiyono; Leny Latifah (International Journal of Nursing and Health Services (IJNHS), 2020)
During this time, the handling of LBW infants in the form of incubator care requires a high cost, while the Kangaroo Mother Care (KMC) has not been able to reach the standard of increase. H-HOPE plus kinesthetic can help parents to care for their baby at home after returning from hospital care. ST36 and SP6 acupressure an essential role in stimulating the production of hormones that affect the absorption of nutrients so that optimal infant growth can be achieved. The study aimed to increase LBW infants' weight using the H-HOPE plus kinesthetic with ST36 and SP6 acupuncture. A randomized control trial (RCT) was applied in this study. We involved 30 LBW infants and divided them into two groups, including the experimental and control groups. The intervention group received the H-HOPE plus Kinesthetic method with acupressure ST36 SP6 for 14 days in 2x/15 minutes/day and KMC 1 hour/day and 15 infants, whereas the control group received the KMC for 14 days in 1 hour/day. The results showed that patients in the experimental group showed increasing the bodyweight within 14 days; approximately 629.33 grams showed p=0.001, meaning that the increase reached the standard of average increase (420 grams). The H-HOPE plus Kinesthetic method with acupressure ST 36 and SP 6 effectively increased LBW infants' weight Keywords : H-HOPE plus Kinesthetic, acupressure, weight, LBW infants.